Idleness Working : the Discourse of Love's Labor from Ovid through Chaucer and Gower - Sadlek, Gregory M., 1950- (Book collections on Project MUSE., 2004)
"Inspired by the critical theories of M.M. Bakhtin, Idleness Working is a groundbreaking study of key works in the Western literature of love from Classical Rome to the late Middle Ages. The study focuses on the evolution of the ideologically-saturated discourse of love's labor contained in these works and thus explores them in context of ancient and medieval theories of labor and leisure, which themselves are seen to evolve through the course of Western history. What emerges from this study is a fresh appreciation and deepened understanding of such well-known classics of love literature as Ovid's Ars amatoria, Andreas Capellanus' De amore, Alan of Lille's Complaint of Nature, Guillaume de Lorris and Jean de Meun's Roman de la rose. John Gower's Confessio Amantis, and Geoffrey Chaucer's Troilus and Criseyde."--Jacket